Knowledge sharing behavior, Islamic work ethic and innovative behavior: entrepreneurial orientation as a moderator - Usman, Muliati (2019)
Innovative behavior is one of the most important aspect to improve quality of public service. Thus, resource such as individual characteristic through specific behavior can be an approach to underpin innovative behavior in the public sector. Therefore, key objective of this study is to explore moderating role of entrepreneurial orientation (EO) on the relationship between knowledge sharing behavior (KSB), and Islamic work ethic (IWE) on innovative behavior (IB) in public sector organization supported by Social Exchange Theory and Social Capital Theory as a foundation. The data were collected through questionnaires from individual manager in public sector in Aceh Province. A total of 192 managers were the sample of the study using cluster sampling technique. This study used Partial Least Squares Structural Equation Modeling (PLS-SEM) to test hypotheses developed for the study. The results of this study proved that innovative behavior is mainly dependent on the level of knowledge sharing behavior, Islamic work ethic and entrepreneurial orientation of individual manager in the public sector. The finding of this study found a direct significant effect of knowledge sharing behavior and Islamic work ethic on innovative behavior. Meanwhile, moderating effect of entrepreneurial orientation can be revealed between knowledge sharing behavior, Islamic work ethic on innovative behavior. Thus, Public sector agencies should emphasize on knowledge sharing behavior, Islamic work ethic and entrepreneurial orientation to enhance innovative behavior among its managers that in return will help improve innovation in public sector. Finally, this study also presents theoretical and practical contributions, as well as limitations and suggestions for future research.